Bio-based green solvent for the catalyst free oxidation of arylboronic acids into phenols - Gupta S.; Chaudhary P.; Seva L.; Sabiah S.; Kandasamy J. (My University, 2025)
A bio-based green solvent, lactic acid, is found to be an efficient reaction medium for the catalyst free oxidation of arylboronic acids into phenols with aqueous hydrogen peroxide. Various substituted arylboronic acids have undergone ipso-hydroxylation smoothly at room temperature to provide corresponding phenols in excellent yields. Remarkably, the oxidation susceptible functional groups such as sulphide, ketone, aldehyde and olefin are tolerated under the reaction conditions. Over all, lactic acid showed higher efficiency as a solvent medium when compared with conventional acetic acid. © The Royal Society of Chemistry 2015.